Scoping Review on Mitigating the Silent Threat of Toxic Industrial Waste: Eco-Rituals Strategies for Remediation and Ecosystem Restoration - Almaw Genet Yeshiwas; Gashaw Melkie Bayeh; Tilahun Degu Tsega; Sintayehu Simie Tsega; Asaye Alamneh Gebeyehu; Zufan Alamrie Asmare; Rahel Mulatie Anteneh; Amare Genetu Ejigu; Ahmed Fentaw Ahmed; Zeamanuel Anteneh Yigzaw; Abathun Temesgen; Anley Shiferaw Enawgaw; et al. (Environmental Health Insights)
Background: The problem of toxic industrial waste impacting soil and water quality remains a significant environmental threat, yet comprehensive solutions are lacking. This review addresses this gap by exploring the effects of industrial waste on ecosystems and proposing strategies for remediation. Its aim is to provide a thorough understanding of the issue and suggest actionable solutions to minimize environmental damage. Methods: A comprehensive scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were sourced from major academic databases, including Science Direct, Scopus, PubMed, Academic Search Premier, Springer Link, Google Scholar, and Web of Science. A total of 105 relevant articles were included based on strict eligibility criteria. The review process encompassed identification, screening, and eligibility checks, followed by data abstraction and analysis. Results: The scoping review highlights the severe impact of toxic industrial waste on soil and water quality, emphasizing pollutants such as heavy metals (cadmium, lead, chromium), organic contaminants, and excess nutrients (nitrogen and phosphorus). These pollutants degrade aquatic ecosystems, causing acidification, eutrophication, and oxygen depletion, leading to biodiversity loss and the mobilization of toxic metals. Soil health is similarly compromised, with heavy metal contamination reducing fertility and disrupting microbial communities essential for nutrient cycling. Mitigation strategies, including cleaner production technologies, effluent treatment, bioremediation, and phytoremediation, offer promising solutions. These eco-friendly approaches effectively reduce pollutants, restore ecosystems, and enhance environmental sustainability, thus mitigating the long-term risks posed by industrial waste on soil and water quality. Conclusions and recommendations: The findings confirm that toxic industrial waste is a critical environmental threat that impacts both aquatic ecosystems and terrestrial soils. Immediate action is necessary to address ecological degradation. Recommended strategies include banning harmful raw materials, pre-treatment of waste, riparian buffering, bioremediation, and stricter regulations to control pollution and safeguard ecosystems.